Industrial training at Maybank Changlun / Siti Nur Raudhah Mohamad Ridzuan - Mohamad Ridzuan, Siti Nur Raudhah (Universiti Teknologi MARA, Perlis, 2024)
Here at Maybank Changlun, I had a memorable and fascinating six months of industrial training that ran from 1 September 2023 to 9 February 2024. Based on my 24-week of internship at Maybank Changlun, this report has been completed. Maybank Changlun is one of Malayan Banking Berhad (Maybank) branches which located in Kedah or Kubang Pasu district. Maybank Changlun’s goal is to be a regional financial services leader. My internship at Maybank Changlun has given me a better understanding of the working world and the ways in which private entity runs its business in order to maximize the profit. In addition, I gain insightful knowledge and worthwhile experience that strengthen my soft skills and boost my self-assurance while interacting with the public. This report aims to analyze Maybank Changlun’s strengths, weaknesses, opportunities, and threats. These include established reputation, wide range of services, dependency on economic conditions, competition, digital banking growth, wealth management, changing customer preferences and economic downturns. I would like to recommend Maybank Changlun with some recommendations. These include the following: Maybank Changlun should encourage industrial training students to demonstrate their abilities in the workplace, hire more staffs to as to cover shortage in manpower at the branch and improve as well as strengthening the organization's reputation.